Pengaruh Ketersediaan Produk dan Kualitas Layanan Digital Terhadap Minat Beli Ulang Pengguna Aplikasi Alfagift PT. Sumber Alfaria Trijaya Tbk di Kecamatan Arcamanik Kota Bandung - Erdi Supandi; Boyke Nugrahanto (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of digital technology has changed consumer behavior in retail shopping through digital applications. This study aims to analyze the effect of product availability and digital service quality on the repurchase intention of Alfagift application users of PT Sumber Alfaria Trijaya Tbk in Arcamanik District, Bandung City. This research employs a quantitative approach using a survey method involving 95 Alfagift application users. The data were analyzed using multiple linear regression with the assistance of IBM SPSS. The results show that product availability and digital service quality have a positive and significant effect on repurchase intention, both partially and simultaneously. Digital service quality has a more dominant influence than product availability. These findings indicate that improving product availability and enhancing digital service quality are important in increasing repurchase intention in digital retail applications.